Metabolite-Based Functional Study of the Bacterium Butyricicoccus pullicaecorum Using Extracellular Fermentation Products - AL-Janahi, Farqad Abdulelah Ali (American Journal of Biology and Natural Sciences, 2025)
In the study, the metabolic activity of Butyricicoccus pullicaecorum was characterized solely through examining extracellular metabolites. The anaerobic base of the bacteria was 72 hours of incubation in a carbohydrate medium, followed by metabolite quantitation at 24, 48, and 72 hours via HPLC and GC–MS. The metabolite composition at 24 hours was dominated by acetate and lactate at 18.4 ± 0.7 mM and 6.1 ± 0.3 mM, respectively, but butyrate was low at 4.8 ± 0.2 mM. By the 48 hours mark, butyrate had climbed to 14.6 ± 0.5 mM and there was a corresponding decrease of lactate to 3.2 ± 0.2 mM, indicative of metabolic conversion. Butyrate reached its highest concentration at the 72 hours mark (26.9 ± 0.9 mM), which was 5.6 times the baseline, and comprised 62% of the total SCFAs. GC–MS was, isolated isobutyrate (1.9 to 4.7 mM), and the 2-methylbutyrate (which was undetectable at 24h, but at 72 had 2.2 mM). Also, the accumulation of the aromatics, specifically 0.8 ± 0.1 mM of the 24h associated phenylacetate to 3.5 ± 0.3 mM of the 72h, and 4-hydroxyphenylacetate which rose from 0.6 to 2.8 mM. Two previously uncharacterized fermentation intermediates, with m/z fragment values of 157 and 171, appeared with 11.2% and 8.4% relative abundance values, respectfully, and were often unaccounted for after the 48-hour mark. From the 24-hour mar, the total number of metabolites produced (32.1 mM) rose significantly at the 72-hour mark (61.4 mM). Data across the timeline affirms the claim that B. pullicaecorum can be entirely characterized with the usage of metabolite only and highlights the butyrogenic capabilities and aromatic fermentation profiles.